A cohort study to investigate the potential indicators for prenatal echocardiographic detection of suspected coarctation of the aorta - Guo, Nan; Zhou, Kaiyu; Li, Yifei; Luo, Shuhua; Liu, Lei; Liu, Hanmin (Frontiers in Cardiovascular Medicine, 2023)
Objectives Suspected coarctation of the aorta (CoA) is a common fetal echocardiographic presentation. However, the prenatal findings did not indicate a satisfied accuracy in determining the truly CoA after birth, which made the prenatal diagnosis of CoA still as a critical challenge with high false positive rate. Thus, this research is aimed to distinguish the potential prenatal parameters influencing the fetal echocardiographic images and enhance the true positive diagnostic rate of CoA fetuses which require early clinical intervention in postnatal life. Methods A retrospective study had been designed and fetuses with suspected with CoA had been included from Jan 2016 to Dec 2021 in our center. The fetal echocardiography and related clinical information had been collected. And the postnatal diagnosis had been reached by echocardiography or CTA. Then, all the parameters had been analyzed by univariate analysis, and a multivariate logistic regression analysis was further involved to determine the independent parameters influencing the accuracy of diagnosis CoA fetuses. Moreover, such results had been validated by nomogram analysis and ROC curve. Results Among the included 44 liveborn infants who presented suspected CoA in fetal cardiac screening, 18 cases had been proved to be CoA postnatally (Group P). The true positive rate for this study was 40.9% (18/44). The abnormal atrial hemodynamic status (AAHs) and the gestational week of delivery (GWoD) were associated with the postnatal CoA confirmation among prenatal suspected fetuses. The ROC curve of predicting probability of the mode combined with two independent factors of absence of AAH and GWoD (AUC = 0.880, 95% CI 0.763–0.997) presented a satisfied efficacy in distinguishing postnatal positive CoA diagnosis. The nomogram plot had been be utilized in CoA prediction (model likelihood ratio test, p < 0.0001). Conclusions AAH and GWoD had been identified as independent factors of predictive accuracy in detecting postnatal CoA among prenatal suspected fetuses. The prediction mode based on nomogram scores could be used to predict the risk of occurring CoA fetuses.